Assessing the effectiveness of buffer zones in logged Malaysia Borneo tropical forests using Tropical Soil Quality Index (TSQI) - Sundara Rajoo, Keeren; Abdu, Arifin; Karam Singh, Daljit Singh; Irie, Mami (Malaysian Soil Science Society, 2024)
Tropical forests face increasing pressure from logging activities, necessitating sustainable management practices to balance economic demands with ecological preservation. This study investigates the effectiveness of buffer zones in maintaining soil quality in logged tropical forests of Sarawak, Malaysia. We compared soil properties and calculated Tropical Soil Quality Index (TSQI) scores across three forest management conditions: natural forest, logged forest with buffer zones, and logged forest without buffer zones. Topsoil samples (0-20 cm depth) were collected from multiple plots within each condition and analyzed for pH, total carbon, total nitrogen, available phosphorus, and exchangeable cations. TSQI scores were calculated following established methods. Results showed that natural forests and logged forests with buffer zones achieved similar TSQI percentages of 50%, while logged forests without buffer zones scored significantly lower at 30%. Buffer zones effectively maintained soil pH, organic carbon, nitrogen, available phosphorus, and exchangeable cations at levels closer to those of natural forests. These findings highlight the importance of buffer zones in mitigating the negative impacts of logging on soil quality. The study provides valuable insights for forest managers and policymakers, supporting the implementation of buffer zones as a key component of sustainable tropical forest management practices. Further research is recommended to assess long-term effects and optimize buffer zone design for maximum soil conservation benefits.